141k views
0 votes
100 POINTS !!!!!!!!!!!!!!!!!!!!!!!!

100 POINTS !!!!!!!!!!!!!!!!!!!!!!!!-example-1

2 Answers

5 votes
remember
x^-m=1/x^m
1/12=12^-1
also
(x^m)^n=x^(mn)
also (x^m)(x^n)=x^(m+n)


( (1)/(12) )^(-2b)(12)^(-2b+2)=12

( 12^(-1))^(-2b)(12)^(-2b+2)=12

( 12^(2b))(12)^(-2b+2)=12

12^(2b-2b+2)=12
12²=12
false
no solution

User Tonny Madsen
by
6.1k points
4 votes

Solution:

(1/12)^(-2b) * 12^(-2b+2) = 12

(12^-1)^(-2b) (12)^(-2b+2) = 12

(12^2b)(12)^(-2b+2) = 12

12^(2b-2b+2) = 12

12^2 = 12

144 does not equal 12

No solution.

Best of Luck!

User Witterquick
by
6.4k points